Polymethyl methacrylate compatible silicon dioxide complexing agent - BARTLETT; KEITH G; CAOLO; MARY A (1985)
An etching solution for the dissolution of silicon dioxide through a portable conformable mask, with PMMA as the etch stop layer, has been developed which eliminates resist lifting and non-uniform lateral etching, thereby providing the improved oxide edge definitions required for 1 micron line geometries in VLSI chips.